White blood cells and coronary heart disease: A mendelian randomization study - Zhao, Qiuping; Liu, Rongmei; Chen, Hui; Yang, Xiaomo; Dong, Jiajia; Bai, Minfu (Frontiers in Genetics, 2023)
Background: The causal direction and magnitude of the associations between blood cell count and coronary heart disease (CHD) remain uncertain due to susceptibility of reverse causation and confounding. This study aimed to investigate the associations between blood cell count and CHD using Mendelian randomization (MR). Methods: In this two-sample MR study, we identified independent blood cell count associated genetic variants from a genome-wide association study (GWAS) among European ancestry individuals. Summary level data of CHD was obtained from a GWAS consisting of 547,261 subjects. Methods of inverse variance weighted (IVW), Mendelian Randomization-Egger (MR-Egger), weighted median, and outlier test (MR-PRESSO) were conducted to investigate the associations between blood cell and CHD. Results: Among all cardiovascular outcomes of interest, blood cell counts were only associated with CHD. Our findings indicated that white blood cell count and neutrophil cell count were significantly associated with increased risk of CHD [odds ratio (OR)=1.07, 95% confidence interval (CI), 1.01-1.14; OR=1.09, 1.02-1.16). However, there was no significant association between monocyte cell count, basophil cell count, lymphocyte cell count, eosinophil cell count, and CHD (P> 0.05). The results after excluding outliers were consistent with main results and the sensitivity analyses showed no evidence of pleiotropy (MR-Egger intercept, P > 0.05) Conclusion: Our MR study suggested that greater white blood cell count and neutrophil cell count were associated with a higher risk of CHD. Future studies are still warranted to validate the results and investigate the mechanisms underlying these associations.